(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2025)
The research aims to demonstrate the role of the reports of the Financial Supervision Bureau in developing and improving the performance of the General Tax Authority by following up on the issued reports and identifying the decisions of the General Tax Authority, its types, methods, effects, causes and the most important procedures followed to achieve them. And preparing financial audit reports in the Federal Financial Supervision Bureau in a way that achieves rationalization of the decisions of the General Tax Authority through the observations monitored by the financial controllers and the field work teams of the Bureau in the General Tax Authority and its branches spread throughout Baghdad. The Sadr City branch was chosen to conduct the analysis and study of the financial reports for the period from 2011 to 2018, which imposes on the auditor the responsibility of performing the audit process and exerting the necessary care and commitment to the quality of the audit, which positively affects the development, efficiency and effectiveness of the performance of the Bureau’s bodies and the quality of their audit reports. One of the most important results reached by the research is that the reports of the Federal Financial Supervision Bureau contribute to consolidating the work of the General Tax Authority and rationalizing its decisions.